Typing of Salmonella spp. Isolated from Chickens in Elazi? Region - Kalender, Hakan; Muz, Adile (My University, 1999)
In this study, 365 chickens slaughtered at a local abattoir and 162 chickens admitted to Elazi? Veterinary Control and Research Institute were investigated for Salmonellosis. Salmonella strains were identified and serogrouped. Antibiotic susceptibility tests were also performed. Fifty seven (10.81%) Salmonella strains were isolated from 527 chickens. Salmonella strains were serogrouped by coagglutination test and slide agglutination test Of 57 strains, 53 were in group D1, 4 were in group B. Of 53 strains in group D1, 39 were serotyped as S. enteritidis and 14 as S. gallinarum. Four strains in group B were serotyped as S. typhimurium. In phagetyping of S. enteritidis strains, 30 of 39 strains were S. enteritidis PT4 and 6 were PT1. One was PT7 and 2 were untypeable. In antibiotic susceptibility tests, most isolates were sensitive to enrofloxacin, gentamycin, neomycin and streptomycin.
Elazi? Bölgesindeki Tavuklardan Izole Edilen Salmonella Türlerinin Tiplendirilmesi
Keywords: Antibiotic sensitivity; Chicken; Phagetyping; Salmonella; Serotyping